Bed-Shear Velocity Measurement in Curved Open Channel - Sumiadi, Sumiadi; Kironoto, Bambang Agus; Legono, Djoko; Istiarto, Istiarto (Fakultas Teknik UB, 2021)
Generally, the condition of the rivers in Indonesia are alluvial rivers which had meanders, where the change in the river bed topography often occur. One of the parameters associated with changes in the river bed topography is bed-shear velocity, or Reynolds stress. The bed-shear velocity can be calculated by the Reynolds stress distribution method and the Clauser method which commonly used in straight channels. In fact, on natural channel there is a curve and even a meandering channel. With more complex flow conditions, the use of the Clauser method in curved channels can be questioned, is it still accurate or not. In this paper, both methods will be discussed by comparing the measurement data in the laboratory using 180ï‚° curved channel with flat bed. The results of data analysis show that the use of these two methods in curved channels produces an average difference of around 19.81%, where the Clauser method gives greater results and better tendencies. Apart from the differences in the results given, it can be said that the Clauser method as well as the Reynolds stress distribution method can still be used to calculate the bed-shear velocity in the curved channel.Â